2003
DOI: 10.1117/1.1528950
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from cervical cells throughout neoplastic progression: influence of nuclear morphology, DNA content, and chromatin texture

Abstract: A number of noninvasive fiber optic optical technologies are under development for real-time diagnosis of neoplasia. We investigate how the light scattering properties of cervical cells are affected by changes in nuclear morphology, DNA content, and chromatin texture, which occur during neoplastic progression. We used a Cyto-Savant computer-assisted image analysis system to acquire quantitative nuclear features measurements from 122 Feulgen-thionin-stained histopathologic sections of cervical tissue. A subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(169 citation statements)
references
References 29 publications
4
165
0
Order By: Relevance
“…neoplastic cells [7,[17][18][19]. Now the reason behind this reflection or scattering of light back from the neoplastic cells was explained by Rebekah Drezek et al, [20] who stated that the longer wavelength light is more transmitted while the shorter wavelength light is more reflected via scattering. The effect is most commonly observed in cells where the protein content increases.…”
Section: Resultsmentioning
confidence: 99%
“…neoplastic cells [7,[17][18][19]. Now the reason behind this reflection or scattering of light back from the neoplastic cells was explained by Rebekah Drezek et al, [20] who stated that the longer wavelength light is more transmitted while the shorter wavelength light is more reflected via scattering. The effect is most commonly observed in cells where the protein content increases.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies examining the optical properties of human tissue have shown that the refractive index of chromatin is significantly different from that of the cytoplasm. 21 These data suggest that the OCT signal will increase with increasing nuclear size and density. Histologically, surface maturation is characterized in part by a decrease in the nuclear to cytoplasmic ratio of the surface epithelium.…”
Section: Description Of Image Scoring Systemmentioning
confidence: 90%
“…9,[16][17][18][19][20] It permits the simulation of scattering from inhomogeneous objects of arbitrary shape. Today it is one of the best fullwave methods for accurate simulations of the scattering of light from a small number of blood cells.…”
Section: A Finite-difference Time-domain Methodsmentioning
confidence: 99%